2021
DOI: 10.3390/atmos12010101
|View full text |Cite
|
Sign up to set email alerts
|

Complex Networks Reveal Teleconnections between the Global SST and Rainfall in Southwest China

Abstract: Droughts and floods have frequently occurred in Southwest China (SWC) during the past several decades. Yet, the understanding of the mechanism of precipitation in SWC is still a challenge, since the East Asian monsoon and Indian monsoon potentially influence the rainfall in this region. Thus, the prediction of precipitation in SWC has become a difficult and critical topic in climatology. We develop a novel multi-variable network-based method to delineate the relations between the global sea surface temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The Yunnan-Guizhou Plateau is located near the tropical oceans of the Bay of Bengal and the South China Sea, where the Indian monsoon and East Asian monsoon bring abundant moisture from the Bay of Bengal, South China Sea, Arabian Sea, and western Pacific, posing challenges to precipitation forecasting in the region [12,13]. Currently, numerous scholars are focused on understanding the connection between sea surface temperature anomalies (SSTA) and precipitation anomalies in the Yunnan-Guizhou Plateau, resulting in a series of meaningful research findings [14,15]. For instance, Jiang et al (2017) [16] employed the EOF method to analyze the primary modes and causes of summer precipitation anomalies in the Yunnan-Guizhou region.…”
Section: Introductionmentioning
confidence: 99%
“…The Yunnan-Guizhou Plateau is located near the tropical oceans of the Bay of Bengal and the South China Sea, where the Indian monsoon and East Asian monsoon bring abundant moisture from the Bay of Bengal, South China Sea, Arabian Sea, and western Pacific, posing challenges to precipitation forecasting in the region [12,13]. Currently, numerous scholars are focused on understanding the connection between sea surface temperature anomalies (SSTA) and precipitation anomalies in the Yunnan-Guizhou Plateau, resulting in a series of meaningful research findings [14,15]. For instance, Jiang et al (2017) [16] employed the EOF method to analyze the primary modes and causes of summer precipitation anomalies in the Yunnan-Guizhou region.…”
Section: Introductionmentioning
confidence: 99%
“…Using complex network methods can capture the elements of the climate system and effectively describe its internal structure (Boccaletti et al, 2006;Zhang et al, 2019;2020b). Over the past several decades, researchers have analysed, understood, and even predicted climate phenomena by the construction of "climate networks" (Wang et al, 2012;Fan et al, 2020;Qiao et al, 2021b). Tsonis et al (2008) constructed a 500-hPa geopotential height field correlation network and found the existence of network supernodes (atmospheric teleconnection) can make the climate system more stable and the transmission of matter and energy more efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Using complex network methods can capture the elements of the climate system and effectively describe its internal structure (Boccaletti et al ., 2006; Zhang et al ., 2019; 2020b). Over the past several decades, researchers have analysed, understood, and even predicted climate phenomena by the construction of “climate networks” (Wang et al ., 2012; Fan et al ., 2020; Qiao et al ., 2021b). Tsonis et al .…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have highlighted the importance of sea surface temperature (SST) forcing on the interannual variability of rainfall over the ESTP (Li et al ., 2018; Qiao et al ., 2021). Furthermore, the El Niño‐Southern Oscillation, the strongest signal of interannual climate variability on Earth, plays a major role in modulating the frequency and intensity of precipitation in China depending on the warming patterns (Li et al ., 2011a; Yuan and Yang, 2012).…”
Section: Introductionmentioning
confidence: 99%